Whole-genome amplification as a tool to improve bacterial detection by PCR in microbiological samples after endodontic treatment - Chianca, Gabriela Ceccon; Fendeler, Caroline Corrêa; Junior, Sérgio Pinto Chaves; Pereira, Gabriella Lorena Dias; Póvoa, Helvécio Cardoso Corrêa; Antunes, Lívia Azeredo Alves; Antunes, Leonardo Santos; Iorio, Natalia Lopes Pontes Póvoa (Frontiers in Oral Health, 2025)
IntroductionMicroorganisms have an important role in the pathogenesis of endodontic disease. Significant advances have been made to increase the sensitivity of microbial detection, identification and enumeration in endodontic samples. The aim of the present study is to compare culture and whole-genome amplification (WGA) followed by PCR assays in the detection of bacteria before and after chemical mechanical preparation (CMP) of root canals.MethodsTen uniradicular teeth with primary endodontic infections were analyzed. Microbiological samples were collected before and after CMP using paper points, which were separated into two groups: (i) culture assay samples were plated onto Brucella agar with 5% defibrinated sheep's blood, menadione and hemin and incubated anaerobically for 14 days at 36°C; (ii) DNA was extracted from molecular assay samples and subject to WGA by isothermal strand displacement with Phi29 DNA polymerase followed by PCR to determine the presence of bacteria.ResultsIn both assays, samples before CMP showed the presence of bacteria in all 10 teeth. After CMP, however, bacterial detection differed in the assays performed (p = 0.0198). The presence of bacteria was detected in 70% (7 of 10) of the samples by WGA followed by PCR, where only 10% (1 of 10) had demonstrated bacterial growth in the culture method.ConclusionThe combination of WGA followed by PCR increased the detection of microorganisms from root canal samples after endodontic treatment using NaOCl as a CMP irrigant. So this combination of techniques can represent an important tool to improve the detection of microorganisms in endodontic research.